2017
DOI: 10.1186/s12913-017-2143-1
|View full text |Cite
|
Sign up to set email alerts
|

Explaining culturally and linguistically diverse (CALD) parents’ access of healthcare services for developmental surveillance and anticipatory guidance: qualitative findings from the ‘Watch Me Grow’ study

Abstract: BackgroundRegular health visits for parents with young children provide an opportunity for developmental surveillance and anticipatory guidance regarding common childhood problems and help to achieve optimal developmental progress prior to school entry. However, there are few published reports from Australian culturally and linguistically diverse (CALD) communities exploring parents’ experiences for accessing child health surveillance programs. This paper aims to describe and explain parental experiences for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 51 publications
4
61
0
Order By: Relevance
“…A more complex picture emerged when we further examined the combination with socioeconomic disadvantage where we found that those children who were not developmentally vulnerable and not disadvantaged (lowest need) and those children who were developmentally vulnerable and not disadvantaged (middle need) had greater odds of using a GP than their developmentally vulnerable and disadvantaged counterparts (highest need). One could argue that although the majority of Australian GPs use Medicare,34 socioeconomic disadvantage remains a barrier to a child using a GP due to other out-of-pocket expenses, cultural barriers and parental health literacy as reported by some service providers and parents 12 35. This may be compounded in the context of developmental vulnerability, where families face a range or additional challenges and stressors and where financial strains may be further stretched because of the higher costs associated with higher care needs.…”
Section: Discussionmentioning
confidence: 99%
“…A more complex picture emerged when we further examined the combination with socioeconomic disadvantage where we found that those children who were not developmentally vulnerable and not disadvantaged (lowest need) and those children who were developmentally vulnerable and not disadvantaged (middle need) had greater odds of using a GP than their developmentally vulnerable and disadvantaged counterparts (highest need). One could argue that although the majority of Australian GPs use Medicare,34 socioeconomic disadvantage remains a barrier to a child using a GP due to other out-of-pocket expenses, cultural barriers and parental health literacy as reported by some service providers and parents 12 35. This may be compounded in the context of developmental vulnerability, where families face a range or additional challenges and stressors and where financial strains may be further stretched because of the higher costs associated with higher care needs.…”
Section: Discussionmentioning
confidence: 99%
“…For infants presenting for immunisation qualitative research has highlighted that GPs may not necessarily ask many WCC questions during these visits [ 17 ]. It is possible that the conversation about WCC may differ for different immunisation visits at different ages.…”
Section: Discussionmentioning
confidence: 99%
“…The implication of this research is that access to WCC is driven by ecological variables of service availability, parent awareness and choice of services, and beliefs about their child’s health. It is, therefore, not surprising that vulnerable populations’ with lower health literacy are less likely to access WCC services than the socially advantaged groups [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…(16) This paper examined household income as the measure of socioeconomic position whereas we used a composite measure that included education and occupation. One could argue that although the majority of Australian GPs do bulk bill using Medicare (30), socioeconomic disadvantage is a barrier to a child accessing a GP due to other out of pocket expenses, cultural barriers, and parental health literacy as reported by some service providers and parents (12,31). If there was true equity we would expect that the highest proportion of children reporting use of a GP in the last 12 months would be children who were developmentally vulnerable and who were disadvantaged, because these children have the highest health and social needs.…”
Section: Use Of Any Health Services By Developmental Vulnerability Anmentioning
confidence: 99%